Complications Associated with Low Position versus Good Position Umbilical Venous Catheters in Neonates of ≤32 Weeks' Gestation - Shahroor, Maher; Maarouf, Ahmad Mustafa; Yang, Jie; Yankanah, Rosanna; Shah, Prakesh S.; Mohamed, Adel (American Journal of Perinatology, 2020)
Objective This study aimed to determine the incidence of umbilical venous catheter associated infection (UVCAI) in very preterm infants based on UVC tip position.Study Design In this retrospective cohort study, infants born at ≤32 weeks were divided into groups with a UVC tip in either a low-lying or good position. The primary outcome was UVCAI. Survival analysis represented time to infection between groups. Subgroup analyses were based on duration of UVC indwelling time.Results Of 1,983 infants, 1,638 infants were eligible; 33% had low-lying UVC and 67% had good position UVC. Survival analyses suggested a significantly higher probability of infection was associated with low UVC (adjusted hazard ratio [HR]: 1.9, 95% confidence interval [CI]: 1.1–3.2; p = 0.001). The risk of infection was higher for UVC of >7 days duration (adjusted HR: 2.2, 95% CI: 1.1–4.2). Extravasation as a complication was significantly higher in the low UVC versus good position UVC (1.3 vs. 0.1%; odds ratio: 14.4, 95% CI: 1.8–119).Conclusion Low-lying UVC was associated with higher risk of infection and extravasation.Key Points
Keywords: umbilical; catheter-related infections; prevention and control; infant; newborn